Human Resource Management In Higher Education Unit Case Study: Trisakti Foundation - I Made Indra P (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The education industry, namely the campus, is an educational service provider industry that acts as a place for preparing quality human resources (HR). The Trisakti Foundation is one of the organizations for higher education in Indonesia which has 6 (six) tertiary institutions, namely Trisakti University, ITL Trisakti, STP Trisakti, STIE Trisakti, STMA Trisakti and STMK Trisakti. These six tertiary institutions have their own uniqueness, but there are gaps in the quality of each of these Higher Education Unit. The quality of tertiary institutions in Indonesia is largely determined by the outcomes of education, research and community service carried out by lecturers and then assessed by the National Accreditation Board for Higher Education (BAN-PT). This study aims to find the causes of differences in the quality of higher education, support systems in terms of HR, and provide suggestions for HR management strategies. This study uses a qualitative method using the Framework of HRM Operational Perspective. Respondents are lecturers, HR managers and research managers at each tertiary institution. Research results get higher education units under the auspices of the Trisakti Foundation have references to staffing regulations. In practice, there are several differences in the development of human resources by each Higher Education Unit. This difference can be seen from the existence of development carried out by the Higher Education Unit or there are some details that are not carried out by the Higher Education Unit. The difference lies in Employee Planning, Employee procurement, Promotion and Transfer and Remuneration.